Online bandwidth provisioning in all optical interconnection networks of data centers: Throughput maximizing approach. (January 2017) - Ebrahimzadeh, Amin; Rahbar, Akbar Ghaffarpour; Alizadeh, Behrooz
Highlights: A dynamic routing and wavelength assignment algorithm is proposed. Network throughput and link utilization are maximized while blocking rate is minimized. Request buffering is used to convert the dynamic traffic into a pseudo-static traffic. Quadratic routing is used to realize the load balancing in the network. Abstract: Blocking rate as the key quality of service (QoS) metric, is traditionally addressed in light-path establishment in wavelength division multiplexed (WDM) optical networks while network throughput and link utilization, on the other hand, are arguably of high significance for network providers. To address this issue, we propose light-path establishment algorithm paying close attention to maximizing the network throughput and also, the total amount of transmitted data while minimizing the blocking rate. The proposed algorithm exploits request buffering to attain pseudo-static traffic out of the dynamic traffic. We also incorporate the load balancing by means of quadratic routing, which in turn, results in further reducing the blocking rate. We develop an analytical framework as well as comprehensive simulations for performance evaluation. Obtained results highlight the fact that the proposed algorithm is capable of efficiently increasing the average link utilization and network throughput while ensuring the desired QoS requirements. Graphical abstract: